Physical activity, screen time, dietary habits, and health outcomes among children and adolescents in the Middle East and North Africa region: a narrative review - Alnaqbi, Shaikha Eisa; Sohail, Rahab; Radwan, Hadia M.; Mohamad, Maysm N.; Zeb, Falak; Hasan, Haydar; Hashim, Mona; Osaili, Tareq; AlBlooshi, Sharifa; Al Dhaheri, Ayesha S.; Stojanovska, Lily; Cheikh Ismail, Leila (Frontiers in Public Health, 2025)
BackgroundPhysical activity (PA) and screen time (ST) are crucial determinants of health among children and adolescents. The Middle East and North Africa (MENA) region has witnessed rapid urbanization, lifestyle transitions, and increased digitalization; all impact PA and ST behaviors. To our knowledge, we aimed to explore the prevalence of PA and ST among children and adolescents in the MENA region, as well as their correlations with health outcomes and dietary practices.MethodsA systematic search was conducted in major databases (Google Scholar, MEDLINE, EMBASE, SPORTdiscus, CINAHL, PsycINFO, and Scopus), 18 eligible studies from 7 countries were included. This narrative review explores the current literature on PA and ST patterns among children and adolescents in MENA, highlighting key trends, determinants, and health outcomes (dietary habits, obesity and overweight, body satisfaction, and quality of life).ResultsStudies indicate that a significant proportion of children and adolescents in the region fail to meet the recommended PA guidelines, with sedentary lifestyles becoming increasingly prevalent. High ST exposure, driven by social media, gaming, and academic screen use, has been linked to unhealthy dietary habits, obesity, and metabolic disorders. This review highlights that boys are generally more physically active than girls. Socioeconomic factors, cultural norms, environmental barriers, and educational demands play crucial roles in shaping PA and ST behaviors.ConclusionsSchool-based interventions, parental influence, and policy measures promoting active lifestyles and accountable screen use are essential to mitigating the negative health effects. However, research gaps persist, particularly in longitudinal studies and intervention effectiveness. Addressing these challenges requires a multidisciplinary approach involving policymakers, educators, health professionals, and communities to foster healthier lifestyles among children and adolescents in the MENA region.